PENERAPAN MODEL PEMBELAJARAN TWO SATAY TWO STRAY TERHADAP HASIL BELAJAR SISWA KELAS VII SMP NEGERI 3 PONTIANAK - Hasanah, Mahfudotun; Buwono, Sri; Ulfah, Maria (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe problem in this research is an attempt to improve the learning outcomes of seventh-grade students of SMP Negeri 3 Pontianak by using the Two Stay Two Stray learning model. This study aimed to determine the learning outcome differences in the use of the Two Stay Two Stray model. This study was conducted in the design of a quasi-experimental with a nonequivalent control group design. The research subjects were students of class VII G and VII I of SMP Negeri 3 Pontianak, each class comprised thirty-one students. The data were collected through direct observation and direct communication techniques. The instruments of data collection were interviews and learning outcomes tests in the form of normative tests. Based on data analysis test, showed that the Asymp value. Sig, 0,000 <0.05, the hypothesis is accepted. The hypothesis test results Ho were rejected and Ha was accepted based on the sig values. Hence, (2-tailed) <0.05 showed a significant difference after using the Two Stay Two Stray learning model. The average score of the experimental class is 91.41 while the control class is 84.51. Therefore, the activity of teaching and learning by using the Two Stay Two Stray model showed significant learning outcomes improvement.Keywords: Learning Outcomes, Learning Model Two Stay Two Stray.